Adipocytokine Regulation and Antiangiogenic Activity Underlie the Molecular Mechanisms of Therapeutic Effects of Phyllanthus niruri against Non-Alcoholic Fatty Liver Disease - Al Zarzour, Raghdaa Hamdan; Alshawsh, Mohammed Abdullah; Asif, Muhammad; Al-Mansoub, Majed Ahmed; Mohamed, Zahurin; Ahmad, Mariam; Majid, Amin Malik Shah Abdul; Asmawi, Mohd Zaini; Kaur, Gurjeet; Al-Dualimi, Dhamraa Waleed; Mun, Fei Yam (MDPI, 2018)
The growth of adipose tissues is considered angiogenesis-dependent during non-alcoholic fatty liver disease (NAFLD). We have recently reported that our standardized 50% methanolic extract (ME) of Phyllanthus niruri (50% ME of P. niruri) has alleviated NAFLD in Sprague–Dawley rats. This study aimed to assess the molecular mechanisms of action, and to further evaluate the antiangiogenic effect of this extract. NAFLD was induced by eight weeks of high-fat diet, and treatment was applied for four weeks. Antiangiogenic activity was assessed by aortic ring assay and by in vitro tests. Our findings demonstrated that the therapeutic effects of 50% ME among NAFLD rats, were associated with a significant increase in serum adiponectin, reduction in the serum levels of RBP4, vaspin, progranulin, TNF-α, IL-6, and significant downregulation of the hepatic gene expression of PPARγ, SLC10A2, and Collα1. Concomitantly, 50% ME of P. niruri has exhibited a potent antiangiogenic activity on ring assay, cell migration, vascular endothelial growth factor (VEGF), and tube formation, without any cytotoxic effect. Together, our findings revealed that the protective effects of P. niruri against NAFLD might be attributed to its antiangiogenic effect, as well as to the regulation of adipocytokines and reducing the expression of adipogenic genes.